Characteristics of Oxide TFT Using Carbon-Doped Ιn2O3 Thin Film Fabricated by Low-Temperature ALD Using Ethylcyclopentadienyl Indium (Ιn-EtCp) and H2O & O3. (3rd July 2019) - Kobayashi, Riku; Nabatame, Toshihide; Kurishima, Kazunori; Onaya, Takashi; Ohi, Akihiko; Ikeda, Naoki; Nagata, Takahiro; Tsukagoshi, Kazuhito; Ogura, Atsushi
Abstract : We investigated characteristic of the In2 O3 films deposited by various atomic layer deposition (ALD) conditions such as growth temperature and doses of InEtCp precursor and H2 O/O3 oxidant gases. A self-limited ALD window was observed in the In2 O3 film deposition when an InEtCp and H2 O/O3 doses were supplied over 27.6 µmol and 0.09/2.94 mmol, respectively, regardless of the growth temperature. The ratio of In:O:C of the In2 O3 films at 150, 170 and 200 ºC were 1:1.16:0.04 (InO1.16 C0.04 ), 1:1.16:0.03 (InO1.16 C0.03 ) and 1:1.2:0 (InO1.2 ), respectively. We found that the carbon-doped (InO1.16 C0.04, InO1.16 C0.03 ) and carbon-free In2 O3 (InO1.2 ) films could be easily deposited by changing the growth temperature. All films had an amorphous structure. The electrical properties of InO1.16 C0.04 TFT changed dramatically from metal-like conductor to semiconductor after post-metallization annealing at 150 ºC in O3 while no InO1.2 TFT changed. This is thought to be due to the suppression of excess oxygen vacancies in InO1.16 C0.04 channel by effect of doped carbon. The InO1.16 C0.04 TFT exhibited superior characteristics of S.S (0.37 V/dec), I on / I off (1.0×10 8 ), V th (3.5 V) and saturation field effect mobility (20.4 cm 2 /Vs). Therefore, carbon-doped Ιn2 O3 is a promising material as a channel of a flexible TFT where low temperature formation is essential.